UnAIDed Class Switching in Activated B-Cells Reveals Intrinsic Features of a Self-Cleaving IgH Locus - Dalloul, Iman; Laffleur, Brice; Dalloul, Zeinab; Wehbi, Batoul; Jouan, Florence; Brauge, Baptiste; Derouault, Paco; Moreau, Jeanne; Kracker, Sven; Fischer, Alain; Durandy, Anne; Le Noir, Sandrine; et al. (Frontiers in Immunology, 2021)
Activation-induced deaminase (AID) is the major actor of immunoglobulin (Ig) gene diversification in germinal center B cells. From its first description, it was considered as mandatory for class switch recombination (CSR) and this discovery initiated a long quest for all of the AID-interacting factors controlling its activity. The mechanisms focusing AID-mediated DNA lesions to given target sequences remain incompletely understood, with regards to the detailed characterization of optimal substrates in which cytidine deamination will lead to double strand breaks (DSBs) and chromosomal cleavage. In an effort to reconsider whether such CSR breaks absolutely require AID, we herein provide evidence showing that this dogma is not absolute in both human and mouse B lymphocytes, based on deep-sequencing approaches. In activated B-cells from either AID-deficient mice or human AID-deficient patients, we report an intrinsic ability of the IgH locus to undergo “on-target” cleavage and subsequent synapsis of broken regions in conditions able to yield low-level CSR. DNA breaks occur in such conditions within the same repetitive S regions usually targeted by AID, but their repair follows a specific pathway with increased usage of microhomology-mediated repair. These data further demonstrate the role of AID machinery as not initiating de novo chromosomal cleavage, but rather catalyzing a process which spontaneously initiates at low levels in an appropriately conformed IgH locus.